Romanian Constitution and Fundamental Civil Rights and Freedoms - Tudorascu, Miruna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the following material, we will try to present some general issues about the Romanian Constitution, but also the main aspects of the fundamental civil rights and freedoms at the constitutional level. A Constitution is the ensemble of rules which points the organization and function of the public authorities, and living in society, so it is important for us to know constitutional aspects. Like the majority of different States Constitutions, the Romanian Constitution begins to settle aspects about Romanian State. We will see, step by step, the issues mentioned in the title of the material how it is framed in our Constitution.
Keywords: Rumunia; konstytucja; prawa podstawowe; wolność; państwo; Romania; constitution; fundamental rights; freedom; state